The Influence of Product Quality on Buying Interest in Tourist Souvenir Shops on the Island of Lombok - Rizki Parabi; Romadhon; Ahmad Nuh (ORGANIZE: Journal of Economics, Management and Finance, 2024)
This study explores the effect of product quality on the buying interest of tourists in souvenir shops in Lombok through a quantitative research approach. Structured questionnaires were administered to a stratified random sample of 100 tourists, evaluating product quality, buying interest, service quality, store ambiance, pricing, and promotional efforts. Data collection occurred both in person and online, and the relationship between product quality and buying interest was examined with control variables like service quality and pricing. Descriptive statistics summarized the demographics, and multiple regression analysis tested the hypotheses, with reliability and validity confirmed by Cronbach's alpha and factor analysis. Ethical considerations included obtaining informed consent and maintaining anonymity. Despite potential limitations such as response bias and the specificity of findings to Lombok, the study validated the questionnaire and showed high reliability. Regression analysis indicated that product features, social influence, personal innovativeness, effort expectancy, and attitude significantly impact purchase intention. The model accounted for a substantial portion of the variance in purchase intention, offering valuable insights for local entrepreneurs and enhancing the understanding of tourism and consumer behavior.